Beyond Skills and Tools: The Critical Role of Psycap and Digital Fluency in Global Competence Development - Herry Sulendro Mangiri; Alfis Pratam; Fuad Abdillah (JURNAL INOVASI PENDIDIKAN DAN SAINS, 2026)
To prepare graduates for global demands, vocational education in Indonesia is strengthening programs such as Factory Teaching and technopreneurship. This study examines how Digital Literacy, Psychological Wealth, Teaching Factory Application, and Technopreneurship affect the Global Competence of vocational school students in Central Java. Data collected from 346 students who actively use digital technology and have completed Field Work Practice were analyzed using an explanatory quantitative approach and a cross-sectional survey design. Structural Equation Modeling with Partial Least Squares (PLS-SEM) in SmartPLS 4 revealed that Digital Literacy (β = 0.531) and Psychological Capital (β = 0.288) have significant direct effects on Global Competence. In contrast, Teaching Factory and Technopreneurship influence Global Competence only indirectly, mediated by Psychological Capital. These findings highlight that digital and psychological skills play a more direct role than formal vocational programs in developing global competencies. The research empirically demonstrates that psychological wealth is a key mediator and that digital literacy, rather than infrastructure, is the main foundation of global competence in the digital age